Ischemic optic neuropathy as a complication of hemodialysis - (:unkn) unknown (My University, 1995)
Optic neuropathy is one of a number of ocular complications occurring in patients with end-stage renal failure receiving hemodialysis. Optic neuropathy may result from uremia or ischemia. We describe the case of a patient with sequential loss of vision in each eye occurring whilst on hemodialysis and associated with hypotension. We postulate an ischemic etiology for this patient's blindness.
Keywords: hemodialysis complication; ischemic optic neuropathy; uremic optic neuropathy